Implementation of Sharia Marketing Strategy for Madura Grocery Stores to Increase the Competitiveness of MSMEs - Ahmad Faqih; Abdur Rohman (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2026)
This study aims to analyze the marketing strategies implemented by Madurese traditional grocery stores (Toko Klontong Madura) in order to enhance competitiveness within the Micro, Small, and Medium Enterprises (MSME) sector. Facing increasingly complex market competition, traditional retail businesses must develop marketing strategies that not only retain loyal customers but also attract new ones. This research adopts a descriptive qualitative approach, using observation, interviews, and documentation for data collection. The findings reveal that personalized customer approaches, flexible pricing, friendly service, and strategic location usage are key factors in sustaining the competitiveness of Madurese grocery stores. The study concludes that appropriate and contextual marketing strategies can strengthen MSMEs amidst the rise of modern retail outlets.